HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT NYERI PEMASANGAN INFUS PADA ANAK USIA PRA SEKOLAH DI IGD RSU GMIM KALOORAN AMURAN - Tengor, Jeaneta; Kallo, Vandry (Journal Of Community & Emergency, 2024)
One of the procedures obtained by children undergoing hospitalization is infusion and blood collection. Where taking blood and infusion will cause pain in the area of infusion needles. Actions taken by nurses to prevent and minimize bodily injury and pain in children undergoing infusion, namely by providing support by family members, nurses providing information related to illness, procedures for actions to be carried out on children. The purpose of this study was to analyze the relationship between family support and the level of infusion pain in pre-school children at the ER GMIM Kalooran Amurang General Hospital. The type of research used in this study is an analytical observational study with a cross sectional design. The population in this study was the number of families and pre-school age children aged 3-6 years as many as 35 people. The sample in this study was non-probability sampling with an accidental sampling method totaling 35 children of pre-school age. Data were analyzed using chi-square statistical test with a value of = 0.015. Based on the results of the study, the relationship between family support and infusion pain levels in pre-school age children at the ER GMIM Kalooran Amurang Hospital using the Chi Square statistical test obtained p-value = 0.015 <0.05. The conclusion in this study, there is a significant relationship between family support and the level of pain in infusion in pre-school children at the ER GMIM Kalooran Amurang General Hospital. Suggestions from this study are that nurses are expected to cooperate with parents when providing more effective family support such as hugging children, communicating with children and providing children's favorite toys to reduce pain when infused.